Harmonization of Tax Criminal Law Enforcement with the New Criminal Code (KUHP): A Restorative Justice Perspective - Silalahi, Heriantonius (Sinergi International Journal of Law, 2025)
This study examines the harmonization of tax criminal law enforcement with the application of restorative justice within the framework of Indonesia's new Criminal Code (KUHP). This reform introduces a new paradigm in criminal law enforcement, focusing on restorative approaches to address tax crimes such as tax evasion, tax avoidance, and aggressive tax planning. This approach aligns with the primary objectives of tax criminal law, namely the recovery of state finances and the deterrent effect, without relying on imprisonment as a primary measure.The main issue addressed in this research is how the harmonization between the criminal provisions in the KUHP and the tax provisions in the General Taxation Provisions and Procedures Law (KUP Law) can create a more effective and inclusive system for enforcing tax criminal law. The research question posed is: How can the application of restorative justice within the harmonized handling of tax crimes in Indonesia enhance taxpayer compliance and expedite the recovery of state finances?The novelty of this research lies in the integration of restorative justice principles into the harmonization of tax criminal law, an area that has not been extensively explored, particularly in relation to the implementation of the new KUHP. The methodology used is a juridical normative approach, supplemented by a comparative analysis of international practices that have successfully implemented restorative justice in tax enforcement.The study finds that the harmonization of restorative approaches with criminal law provisions can improve tax compliance, reduce litigation burdens, and offer more effective solutions for financial recovery. Therefore, the application of restorative justice in tax crimes could be a crucial step in the legal reform process in Indonesia.